Production of volatile phenols by Lactobacillus plantarum in wine conditions - Fras, Pauline (2014)
Some lactic acid bacteria produce volatile phenols in culture medium but this activity has not been extensively studied in wine conditions. Red and white wines were mixed with MRS medium at different ratios to study the influence of wine on the metabolism of p-coumaric and ferulic acids by Lactobacillus plantarum. In MRS broth supplemented with these precursors at 10 mg l-1, only 4-ethylphenol was produced (1 mg l-1) while, in the presence of wine, 4-vinylphenol was also obtained. Both volatile phenols are produced in nearly equal amounts (1 mg l-1) or almost only 4-vinylphenol depending on the MRS:wine ratio. Thus, wine favours the accumulation of 4-vinylphenol. Ferulic acid was not or was weakly metabolized in the conditions studied.